Panoramic Radiography, Diagnosis and Abnormalities. - Amera K Khalil (University of Mosul, College of Dentistry, 2008)
Aim: To find the importance of panoramic radiograph as aid in iagnosis, prognosis and determination of treatment complexity.Materials and Methods: This study was conducted among (132) panoramic radiographs of males and females which were nearly equal in numbers. The mean age of males was (36.73) years and the mean age of the females was ( 29.82) years. Result: Among these radiographs (0.75%) showed edentulous upper and lower ridges, ( 0.75%) showed multiple dental implants, (1.51%) showed fixative appliance, ( 8.33%) showed fixed bridges, ( 9.84%) showed retained roots, (16.66%) showed endodontically treated teeth, (5.3%) showed radiopaque lesions. The dental caries experience of the total patients were (6.92) for D3MFT and (4.07) for D3FS. The majority of caries experience was found in permanent molars. The percentage of radiograph that showed microdontia and congenital missing teeth were (4.54%) and (10.6%) respectively, the number of males was higher than that of females and mostly related to third molars. The percentage of hyperdontia (0.75%), dilacerations (4.54%), concrescence (0.75%). The number of impacted teeth in females was higher than that in males with statistically significant difference. Conclusion:The panoramic survey is necessary for all patients.